Analisis Perlindungan Hukum Terhadap Anak Korban Kekerasan Seksual di Dinas Pemberdayaan Perempuan dan Perlindungan Anak Kota Tanjungbalai - Adila, Putri Rahma; Hadiningrum, Sri (CV. Rayyan Dwi Bharata, 2024)
The aim of this research is to find out how the Office of Women's Empowerment and Child Protection has attempted to implement legal protection in accordance with Law Number 35 of 2014 concerning Amendments to Law Number 23 of 2002 concerning Child Protection against cases of sexual violence against children, as well as to find out efforts made by the Tanjung Balai City Women's Empowerment and Child Protection Service to help child victims of sexual violence. This research was conducted at the Women's Empowerment and Child Protection Service in Tanjungbalai City, North Sumatra. The method used in this research is a qualitative descriptive research method. The qualitative descriptive method has the main characteristics, namely conducting research involving direct involvement in the field, acting as an observer, creating categories of actors, observing phenomena, recording them in an observation book, not manipulating variables, and focusing on scientific observation. The data collection technique used to obtain data is through interviews and documentation. The results of this research found that the efforts of the Tanjung Balai City Women's Empowerment and Child Protection Department have been running optimally, in accordance with Law Number 35 of 2014 concerning Amendments to Law Number 23 of 2002 concerning Child Protection against cases of sexual violence against children. The form of legal protection used is in the form of preventive and repressive legal protection. One of the programs being implemented is synchronizing and coordinating the prevention of violence against children, which is expected to reduce the number of cases of sexual violence against children in Tajung Balai City.